Integrating invasion and disease in the risk assessment of live bird trade. Issue 1 (13th November 2014) - Springborn, Michael R.; Keller, Reuben P.; Elwood, Sarah; Romagosa, Christina M.; Zambrana‐Torrelio, Carlos; Daszak, Peter
Abstract: Aim: International trade in plants and animals generates significant economic benefits. It also leads to substantial unintended impacts when introduced species become invasive, causing environmental disturbance or transmitting diseases that affect people, livestock, other wildlife or the environment. Policy responses are usually only implemented after these species become established and damages are already incurred. International agreements to control trade are likewise usually based on selection of species with known impacts. We aim to further develop quantitative invasive species risk assessment for bird imports and extend the tool to explicitly address disease threats. Location: United States of America. Methods: We use a two‐step approach for rapid risk assessment based on the expected biological risks due to both the environmental and health impact of a potentially invasive wildlife species in trade. We assess establishment probability based on a model informed by historical observations and then construct a model of emerging infectious disease threat based on economic and ecological characteristics of the exporting country. Results: We illustrate how our rapid assessment tool can be used to identify high‐priority species for regulation based on a combination of the threat they pose for becoming established and vectoring emerging infectious diseases. Main conclusions: Our approach can be executed for a species in a matter of days and is nested in an economic decision‐making framework for determining whether the biological risk is justified by trade benefits.